Potential Impacts of Aerosol on Diurnal Variation of Precipitation in Autumn Over the Sichuan Basin, China. Issue 13 (6th July 2022) - Liu, Jiajun; Zhao, Chuanfeng; Lin, Yanluan; Zhang, Qiang; Liu, Huan; Xiao, Qingyang; Peng, Yiran
Abstract: This study investigates the autumn precipitation in Sichuan Basin (SB), China in combination with reanalysis data sets of aerosol and meteorological fields from 2008 to 2018. To identify the aerosol impacts on precipitation, we carefully selected and divided the data into multiple groups according to vorticity, precipitation amount category, aerosol pollution level, and the geopotential height (GH) in the upper troposphere. Our data show that the precipitation in SB are generally reduced and weakened in afternoon to evening, but enhanced and intensified after midnight under the aerosol polluted condition. By analyzing data contrasts between different groups, we find that aerosol pollution in SB reduces shortwave heating near surface, which enhances the tropospheric stability and inhibits the vertical motion and rainfall in the afternoon to early evening. As the stability reduces within the basin, the vertical motions are invigorated to enhance and intensify the rain after midnight. Therefore, we conclude that the aerosol pollution in SB and the rapid adjustment of aerosol‐radiation interaction amplify the diurnal features of precipitation in autumn. Plain Language Summary: The present study illustrates that aerosols modify atmospheric thermodynamic states by direct effects and further impact diurnal variation of precipitation over the Sichuan Basin (SB). Key Points: Precipitation in Sichuan Basin are reduced and weakened in the afternoon and evening but enhanced and intensified after midnight Aerosol pollution reduces shortwave heating at the surface, enhances tropospheric stability, and inhibits vertical motion in the afternoon The rapid adjustment of aerosol‐radiation interaction amplifies the diurnal evolution of thermodynamic and precipitation features